Antioxidant Activities and Bioactive Compound in The Extract of Lobophytum sp. - A. Mu’nisa (Bionature, 2023)
This study is a descriptive exploratory research that aims to know the activity of soft coral Lobophytum sp. extractas an antioxidant. Sample extraction was done by maceration using methanol. Viscous extract obtained was thenpartitioned using n-hexane until gained methanol and n-hexane fraction. The chemical compositions of themethanol extract of Lobophytum sp were investigated using Gas chromatography-Mass spectrometry. The yieldresult of soft coral Lobophytum sp. extract is 2,59%. The weight of extract partition result were methanol fraction8,76 g and n-hexane fraction 1,02 g. Antioxidant activity test using the 2,2-Diphenyl-1-picrylhydrazyl (DPPH)assay. Ascorbic acid was also used as positive antioxidant control. The percentage of inhibition and IC50 weremeasured. Antioxidant activity test which gains the best antioxidant activity is methanol fraction then followed byn-hexane fraction, both showed DPPH free radical 50% can be inhibited the activity with IC50 rate in a sequence16,93 ppm and 30,93 ppm. GC-MS analysis, 50 kinds of chemical composition are identified in the Lobophytumsp. The results showed that the soft coral extracts of Lobophytum sp. has antioxidant activity.